Characteristics of iron status, oxidation response, and DNA methylation profile in response to occupational iron oxide nanoparticles exposure. (March 2020) - Yu, Min; Zhou, Xingfan; Ju, Li; Yu, Man; Gao, Xiangjing; Zhang, Meibian; Tang, Shichuan
Although the growing development and application of iron oxide nanoparticles (IONPs) may pose exposure risk and adverse health outcomes, biological changes due to occupational exposure remain unexplored. This cross-sectional study recruited 23 workers at a plant that manufactures IONPs and 23 age- and sex-matched controls without metal-rich occupational hazards exposure. Exposure metrics at worksites were monitored, and iron status, oxidation markers, and methylation profiles of genomic DNA in peripheral blood were measured using corresponding enzyme-linked immunosorbent assays and methylation-specific polymerase chain reaction (PCR), respectively. The mass concentration, number counting, and surface area concentration of airborne particles at the worksite significantly increased during the work process of manufacturing/handling IONPs. Overall, compared to controls, workers exhibited increased 5-hydroxymethylcytosine (5hmC) levels without changes in 5-methylcytosine (5mC), hepcidin methylation, iron, soluble transferrin receptor (sTfR), ferritin, hepcidin, 8-hydroxydeoxyguanosine, and glutathione. A positive correlation was found between 5hmC and IONP exposure year with adjustment for age, sex, and cotinine using partial correlation analyses ( r = 0.521, p < 0.001). After stratification of INOPs exposure and 5hmC levels, the univariate general linear model with adjustment for age, sex, and cotinine found that the estimated mean levels of 5mC and sTfR in subjects with low and high 5hmC levels among controls were 11% and 14.4% ( p ≤ 0.01) and 80.9 nM and 70.3 nM ( p < 0.05), respectively. The estimated mean levels of sTfR in workers and controls with low 5hmC levels were 88.3 nM and 68.7 nM ( p ≤ 0.01). Multivariate linear regression analyses suggested an association between sTfR and 5hmC (standardized β = −0.420, p = 0.014) and female sex (standardized β = 0.672, p < 0.001) for subjects with low 5hmC levels. These findings suggest that increased 5hmC could be differentially employed to monitor an epigenetic signature with steady iron homeostasis for occupational IONP-exposed individuals who are likely to experience early but specific decreased sTfR, especially for females concurrent with the onset of increment in 5hmC at low level.